Особливості підготовки лікаря загальної практики з офтальмогії - Сухіна, Л.О.; Голубов, К.Є.; Смирнова, О.Ф.; Зоріна, М.Б.; Сухіна, І.В.; Котлубей, Г.В. (Таврический медико-биологический вестник, 2012)
В работе приводятся данные об особенностях преподавания офтальмологии врачам общей практики- семейная медицина, в условиях реформирования здравоохранения. Делается акцент на использовании информационно-комуникативных технологий в процессе последипломной обучения, которые, прежде всего, способствуют развитию творческого мышления врача In the data provided by the training of general practitioners on ophthalmology. The paper provided data on the characteristics of the teaching of ophthalmology in health care reform. emphasis on spreading use of information and communication technology in education likariyav general practice of ophthalmology, which aim, above all, the development of creative thinking doctor.